Tailoring the electrochemical properties of carbon nanotube modified indium tin oxide via in situ grafting of aryl diazonium - Hicks, Jacqueline; Wong, Zhi Yi; Scurr, David J.; Silman, Nigel; Jackson, Simon K.; Mendes, Paula M.; Aylott, Jonathan W.; Rawson, Frankie J. (American Chemical Society, 2017)
Our ability to tailor the electronic properties of surfaces by nanomodification is paramount for various applications, including development of sensing, fuel cell, and solar technologies. Moreover, in order to improve the rational design of conducting surfaces, an improved understanding of structure/function relationships of nanomodifications and effect they have on the underlying electronic properties is required. Herein, we report on the tuning and optimization of the electrochemical properties of indium tin oxide (ITO) functionalized with single-walled carbon nanotubes (SWCNTs). This was achieved by controlling in situ grafting of aryl amine diazonium films on the nanoscale which were used to covalently tether SWCNTs. The structure/function relationship of these nanomodifications on the electronic properties of ITO was elucidated via time-of-flight secondary ion mass spectrometry and electrochemical and physical characterization techniques which has led to new mechanistic insights into the in situ grafting of diazonium. We discovered that the connecting bond is a nitro group which is covalently linked to a carbon on the aryl amine. The increased understanding of the surface chemistry gained through these studies enabled us to fabricate surfaces with optimized electron transfer kinetics. The knowledge gained from these studies allows for the rational design and tuning of the electronic properties of ITO-based conducting surfaces important for development of various electronic applications.